PENGARUH PERPUTARAN PIUTANG TERHADAP RETURN ON ASSET (ROA) PADA PT. SUBUR MEKAR ABADI KABUPATEN TAPANULI TENGAH - Siti Nurmala Sari Dewi; Safriadi Pohan; Yusi Tri Utari Panggabean (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2022)
This study aims to examine the effect of accounts receivable turnover on return on assets at PT. Subur Mekar Abadi. The author uses research methods in quantitative descriptive to discuss the problems faced by corporate finance. Data analysis described the use of the results of several linear sub-data analyzes regarding receivable turnover on return on assets (Y). The results showed that there was a negative relationship between banana turnover and return on assets at PT. Subur Mekar Abadi of 0.793, so when interpreted on a value scale it can be categorized as very strong. The regression equation obtained Y = 0.727 -0.22 X which shows the effect of accounts receivable turnover on return on assets at PT. Subur Mekar Abadi. The t test shows that the proposed hypothesis is rejected (not significant), where t count is -2.255 > 2.07387, which means that the turnover of accounts receivable is not necessarily reduced by the regression coefficient/slop (0.22) if the variable turnover of accounts receivable is added by one unit. While the coefficient of determination is known that accounts receivable turnover only plays a role of 62.9% of the return on assets at PT. Subur Mekar Abadi and the remaining 37.1% are influenced by other factors not included in the model.